Clinical Significance of Variants in the TTN Gene in a Large Cohort of Patients With Sporadic Dilated Cardiomyopathy - Xiao, Lei; Li, Chenze; Sun, Yang; Chen, Yanghui; Wei, Haoran; Hu, Dong; Yu, Ting; Li, Xianqing; Jin, Li; Shi, Leming; Marian, Ali J.; Wang, Dao Wen (Frontiers in Cardiovascular Medicine, 2021)
Background: Mutations in the TTN gene are the most common causes of dilated cardiomyopathy (DCM). The clinical significance of TTN gene variants remains inadequately understood. Methods: Whole-exome sequencing and phenotypic characterisation were performed, and patients were followed up for a median of 44 months. Results: We analyzed the association of the TTN variants with the clinical outcomes in a prospective study of 1,041 patients with sporadic DCM. TTN truncating variants (tTTN) were detected in 120 (11.5%) patients as compared with 2.4/10,000 East Asian populations in the Genome Aggregation Database (GnomAD; p < 0.0001). Pathogenic TTN missense variants were also enriched in DCM as compared with the GnomAD populations (27.6 vs. 5.9%, p < 0.0001). DCM patients with tTTN had a lower left ventricular ejection fraction (28.89 ± 8.72 vs. 31.81 ± 9.97, p = 0.002) and a lower frequency of the left bundle branch block (3.3 vs. 11.3%, p = 0.011) than those without or with mutations in other known causal genes (OCG). However, tTTN were not associated with the composite primary endpoint of cardiac death and heart transplantation during the follow-up period [adjusted hazard ratio (HR): 0.912; 95% confidence interval: 0.464–1.793; p = 0.790]. There was also no sex-dependent effect. Concomitant tTTN and pathogenic variants in OCG were present in only eight DCM patients and did not affect the outcome. Conclusion: The phenotype of DCM caused by tTTN, major causes of sporadic DCM, is not distinctly different from those caused by other causal genes for DCM.